Extending the utility of [Pd(NHC)(cinnamyl)Cl] precatalysts: Direct arylation of heterocycles - Martin, Anthony R.; Chartoire, Anthony; Slawin, Alexandra M. Z.; Nolan, Steven P. (Beilstein Journal of Organic Chemistry, 2012)
The use of [Pd(NHC)(cinnamyl)Cl] precatalysts in the direct arylation of heterocycles has been investigated. Among four different precatalysts, [Pd(SIPr)(cinnamyl)Cl] proved to be the most efficient promoter of the reaction. The C–H functionalization of sulfur- or nitrogen-containing heterocycles has been achieved at low catalyst loadings. These catalyst charges range from 0.1 to 0.01 mol % palladium.
Keywords: C–H functionalization; direct arylation; heterocycles; N-heterocyclic carbenes; palladium

(untitled) - Neufeldt, S. R.; Sanford, M. S. (Acc. Chem. Res., 2012)

(untitled) - Newhouse, T.; Baran, P. S. (Angew. Chem., Int. Ed., 2011)

(untitled) - Ackermann, L. (Chem. Rev., 2011)

(untitled) - Bellina, F.; Rossi, R. (Tetrahedron, 2009)

(untitled) - Joucla, L.; Djakovitch, L. (Adv. Synth. Catal., 2009)

The chemistry of Heterocycles: Structure, Reactions, Syntheses, and Applications - Eicher, T.; Hauptmann, S.; Speicher, A. (Wiley-VCH, 2003)

(untitled) - Dua, R.; Shrivastava, S.; Sonwane, S. K.; Srivastava, S. K. (Adv. Biol. Res., 2011)

(untitled) - Alberico, D.; Scott, M. E.; Lautens, M. (Chem. Rev., 2007)

(untitled) - Kumar, P. V.; Lin, W.-S.; Shen, J.-S.; Nandi, D.; Lee, H. M. (Organometallics, 2011)

(untitled) - Demir, S.; Özdemir, İ.; Arslan, H.; VanDerveer, D. (J. Organomet. Chem., 2011)

(untitled) - Chan, K.-T.; Tsai, Y.-H.; Lin, W.-S.; Wu, J.-R.; Chen, S.-J.; Liao, F.-X.; Hu, C.-H.; Lee, H. M. (Organometallics, 2010)

(untitled) - Lane, B. S.; Brown, M. A.; Sames, D. (J. Am. Chem. Soc., 2005)

(untitled) - Touré, B. B.; Lane, B. S.; Sames, D. (Org. Lett., 2006)

(untitled) - Normand, A. T.; Cavell, K. J. (Eur. J. Inorg. Chem., 2008)

(untitled) - Joo, J. M.; Touré, B. B.; Sames, D. (J. Org. Chem., 2010)

(untitled) - Ozdemir, İ.; Gök, Y.; Özeroğlu, Ö.; Kaloğlu, M.; Doucet, H.; Bruneau, C. (Eur. J. Inorg. Chem., 2010)

(untitled) - Marion, N.; Navarro, O.; Mei, J.; Stevens, E. D.; Scott, N. M.; Nolan, S. P. (J. Am. Chem. Soc., 2006)

(untitled) - Navarro, O.; Marion, N.; Mei, J.; Nolan, S. P. (Chem.–Eur. J., 2006)

(untitled) - Marion, N.; Nolan, S. P. (Acc. Chem. Res., 2008)

(untitled) - Egbert, J. D.; Chartoire, A.; Slawin, A. M. Z.; Nolan, S. P. (Organometallics, 2011)

(untitled) - Chartoire, A.; Lesieur, M.; Falivene, L.; Slawin, A. M. Z.; Cavallo, L.; Cazin, C. S. J.; Nolan, S. P. (Chem.–Eur. J., 2012)

(untitled) - Chartoire, A.; Frogneux, X.; Nolan, S. P. (Adv. Synth. Catal., 2012)

(untitled) - Berthon-Gelloz, G.; Siegler, M. A.; Spek, A. L.; Tinant, B.; Reek, J. N. H.; Markó, I. E. (Dalton Trans., 2010)

(untitled) - Poater, A.; Cosenza, B.; Correa, A.; Giudice, S.; Ragone, F.; Scarano, V.; Cavallo, L. (Eur. J. Inorg. Chem., 2009)

(untitled) - Ohta, A.; Akita, Y.; Ohkuwa, T.; Chiba, M.; Fukunaga, R.; Miyafuji, A.; Nakata, T.; Tani, N.; Aoyagi, Y. (Heterocycles, 1990)

(untitled) - Nandurkar, N. S.; Bhanushali, M. J.; Bhor, M. D.; Bhanage, B. M. (Tetrahedron Lett., 2008)

(untitled) - Tamba, S.; Okubo, Y.; Tanaka, S.; Monguchi, D.; Mori, A. (J. Org. Chem., 2010)

(untitled) - Liégault, B.; Lapointe, D.; Caron, L.; Vlassova, A.; Fagnou, K. (J. Org. Chem., 2009)

(untitled) - Baghbanzadeh, M.; Pilger, C.; Kappe, C. O. (J. Org. Chem., 2011)

(untitled) - Martins, A.; Alberico, D.; Lautens, M. (Org. Lett., 2006)

(untitled) - Martins, A.; Lautens, M. (J. Org. Chem., 2008)

(untitled) - Takeda, D.; Yamashita, M.; Hirano, K.; Satoh, T.; Miura, M. (Chem. Lett., 2011)

(untitled) - Ohno, H.; Iuchi, M.; Fujii, N.; Tanaka, T. (Org. Lett., 2007)

(untitled) - Fournier Dit Chabert, J.; Gozzi, C.; Lemaire, M. (Tetrahedron Lett., 2002)

(untitled) - David, E.; Perrin, J.; Pellet-Rostaing, S.; Fournier Dit Chabert, J.; Lemaire, M. (J. Org. Chem., 2005)

(untitled) - David, E.; Pellet-Rostaing, S.; Lemaire, M. (Tetrahedron, 2007)

(untitled) - Kelly, R. A., III; Clavier, H.; Giudice, S.; Scott, N. M.; Stevens, E. D.; Bordner, J.; Samardjiev, I.; Hoff, C. D.; Cavallo, L.; Nolan, S. P. (Organometallics, 2008)

(untitled) - Dorta, R.; Stevens, E. D.; Scott, N. M.; Costabile, C.; Cavallo, L.; Hoff, C. D.; Nolan, S. P. (J. Am. Chem. Soc., 2005)

(untitled) - Fantasia, S.; Petersen, J. L.; Jacobsen, H.; Cavallo, L.; Nolan, S. P. (Organometallics, 2007)

(untitled) - Gusev, D. G. (Organometallics, 2009)

(untitled) - Lapointe, D.; Markiewicz, T.; Whipp, C. J.; Toderian, A.; Fagnou, K. (J. Org. Chem., 2011)

(untitled) - Požgan, F.; Roger, J.; Doucet, H. (ChemSusChem, 2008)

(untitled) - Roger, J.; Požgan, F.; Doucet, H. (Green Chem., 2009)

(untitled) - Fu, H. Y.; Chen, L.; Doucet, H. (J. Org. Chem., 2012)